Draping for apparel design - Joseph-Armstrong, Helen; Ashdown, S. P. (Susan P.) (New York Fairchild Books, 2022)
"Draping for Apparel Design, Fourth Edition is the fully updated and revised edition of the seminal book pioneered by fashion education luminary Helen Joseph-Armstrong. This comprehensive guide provides step-by-step instruction for the beginning patternmaker and advanced techniques for the more experienced. Maintaining the vast array of examples and the book's easy-to-read style, revising author Susan Ashdown reflects current industry standards, both metric and imperial measurements, new sizing guides for diverse body types, and incorporates half-scale forms. New material on jackets, coats, and loose fitted knitwear add to this book's breadth of knowledge"--
Chapter 1. Tools and supplies for draping -- Chapter 2. Textile materials: the spirit and structure of design -- Chapter 3. The body and the dress from: preparation for draping -- Chapter 4. Essential draping skills -- Chapter 5. Draping the basic silhouette -- Chapter 6. The concepts of dart manipulation and dart equivalents -- Chapter 7. Bodice styles -- Chapter 8. Skirts -- Chapter 9. Dress foundations and designs -- Chapter 10. Pants -- Chapter 11. Collars -- Chapter 12. Kimono, raglan, and drop shoulder -- Chapter 13. Shirts and blouses -- Chapter 14. Built-up necklines -- Chapter 15. Cowls -- Chapter 16. Strapless dress foundations and corsets -- Chapter 17. Bias cut dresses and twist styles -- Chapter 18. Jackets and coats -- Chapter 19. Cut and sew knit styles.
Includes bibliographical references and index.
Keywords: Garment cutting; Dressmaking -- Pattern design